Developing the Qualimetric Competence of the Undegraduate Bachelors - Prospective Teachers - Y. A. Shikhov; O. F. Shikhova; V. V. Yushkovna (Образование и наука)
The paper is devoted to the technology of qualimetric competence formation of undergraduate pedagogic students training for the bachelor degree. The author regards the qualimetric competence as the complex of expertise, skills, and abilities necessary for successful professional activities, related to student assessment and training quality control. The structure of the above competence includes the following set of components: organizational, managerial, control and evaluation, informational, analytical and personal.The paper provides the characteristics of the “Educational Quality Control” course designed for the bachelor students specializing in Technological Education. The opportunities for using the case technology both in classroom and as the self study work are described along with the options of cases and the criteria for their evaluation. According to the author, it is advisable to use the group peer review method as the key one in quality measurement. The implementation results of the above course demonstrate the positive dynamics in qualimetric competence formation of the future bachelors in Technological Education.